Development of VHF LC-Passive Filters for Multiband Transient Radio Telescope - Anwar, Radial; Tariqul Islam, Mohammad; Misran, Norbahiah; Gopir, Geri (IJAIT (International Journal of Applied Information Technology), 2017)
Filter is one of key module in a radio telescope system. This article present the development of VHF LC-passive filters meant to support a multiband antenna in a transient radio telescope system by reducing the bandwidth of each operating frequencies. The filters were developed by employing low-cost inductor and capacitor with low self-resonant frequency (SRF) an hence the characteristic are highly affected by the parasitic inductance of the capacitors an parasitic capacitance of the inductors. Therefore, general equation to develop an LC filters was no longer applicable in developing these filters. Nevertheless, three filters were successfully developed, operated at 38 MHz, 74 MHz and 152 MHz with relatively good quality factors up to of about 13.